Ethical dimension of scientific investigation (Práxis Educativa, 2014)
After emphasizing the growing concern about ethical issues related to scientific research involving human subjects by bodies responsible for the promotion of science in Brazil, this paper discusses the different perspectives under which relationships between ethics and production knowledge are established, highlighting the close connection of the ethical dimension to the political dimension, given the need for affirmation of otherness, for the presence of the other, so that one can discuss the ethical quality of any human action. It is concluded that initiatives aiming at standardizing procedures of scientific research are legitimated as important means to ensure respect for human dignity in the scientific practice. Keywords: Ethics. Research. Regulation.